2011
DOI: 10.1007/s10901-011-9216-y
|View full text |Cite
|
Sign up to set email alerts
|

Social housing programme of Selangor Zakat Board of Malaysia and housing satisfaction

Abstract: Social housing in Malaysia is provided through the public and private sectors. Recently, the Selangor Zakat Board (SZB) has started to provide social housing in the state of Selangor, Malaysia. Up to 2007, a total of 906 units have been delivered under its different programmes. This paper evaluates these programmes by adopting the housing satisfaction model which is currently used as a customer satisfaction tool for public/private housing in many local governments in the UK and USA. The main purpose of this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 23 publications
2
49
0
7
Order By: Relevance
“…Mohit, et al (2010), studied residential satisfaction of newly designed public low-cost housing and found that the residents are moderately satisfied with dwelling unit supporting services, followed by public and neighborhood facilities than dwelling unit features and social environment. Mohit and NurulNazyddah (2011) studied Selangor Zakat Board-funded low income housing in Selangor State and found that the agency has been successful in providing a moderate level of satisfaction with three types of housing units in the State.…”
Section: Qol Research In Malaysiamentioning
confidence: 99%
“…Mohit, et al (2010), studied residential satisfaction of newly designed public low-cost housing and found that the residents are moderately satisfied with dwelling unit supporting services, followed by public and neighborhood facilities than dwelling unit features and social environment. Mohit and NurulNazyddah (2011) studied Selangor Zakat Board-funded low income housing in Selangor State and found that the agency has been successful in providing a moderate level of satisfaction with three types of housing units in the State.…”
Section: Qol Research In Malaysiamentioning
confidence: 99%
“…Em que pese o grande avanço dos estudos e pesquisas sobre APO em termos de procedimentos metodológicos, tendo-se em mente a qualidade no processo de projeto, produção, uso, operação e manutenção de ambientes construídos, especialmente no caso da habitação social (ABIKO; ORNSTEIN, 2002;ONO, 2010;RHEINGANTZ et al, 2009;ORNSTEIN, 2013;SARAMAGO;GARCIA, 2015;LAY;REIS, 2005), pouco dessa expertise foi efetivamente aplicada às políticas públicas e à prática profissional no âmbito habitacional no Brasil, como ocorreu em outros países (MOHIT;NAZYDDAH, 2011;JANSEN, 2012). Nessa perspectiva, uma parte do projeto INOVATEC-FINEP se propõe a fazer uma ponte metodológica entre os instrumentos de APO específicos para a avaliação em uso de conjuntos habitacionais produzidos com sistemas construtivos inovadores e aqueles instrumentos aplicados de forma mais convencional, nas últimas décadas (FABRICIO, ONO, 2015).…”
Section: A Apo E a Avaliação Integrada De Desempenho De Sistemas Consunclassified
“…Desde una perspectiva psicoambiental, la Satisfacción Residencial es una evaluación de aproximación cualitativa normativa y noeconómica que se usa para estimar la calidad de los servicios y unidades de la vivienda (Mohit, 2011). Se sustenta en la idea de que los niveles de satisfacción reflejan el espacio entre la realidad del sujeto y sus expectativas (Campbell et al 1976).…”
Section: El Estudio De Los Vínculos Socioespacialesunclassified